Critical Analysis of the Use of a Statistical Test in a Research Document (Linear Regression Test) - Salif BALDE (Journal of Advanced Research in Education, 2023)
This article takes a critical look at a text written with a quantitative methodological approach (with the use of a statistical test). This is the text of Michaelowa (2000), on “Educational expenditure, quality of education and poverty: the example of five French-speaking African countries”. Indeed, most scientific articles and other research reports are written with a qualitative or quantitative approach (with the use of a statistical test). It would therefore be interesting to take a critical look at these texts, because as soon as research includes a presentation of results, it is possible to pass judgment on the methodology used. In the context of this work, the critical eye focuses on the use of the Linear Regression test.